2018
DOI: 10.1002/bjs.10828
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre randomized clinical trial of the effect of chewing gum after abdominal surgery

Abstract: The addition of chewing gum to an ERAS postoperative care pathway after elective abdominal surgery does not reduce the LOS, time to bowel recovery or the rate of postoperative complications. Registration number: NTR2594 (Netherlands Trial Register).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 53 publications
0
34
0
3
Order By: Relevance
“…The evidence, however, was considered to be of low quality and limited external validity, owing to small sample sizes (with the average number of patients per trial ranging from 20 to 50), the absence of a perioperative ERPs setting and the limited diversity of surgical procedures. The results of this review have also since been refuted by a recent large multicentre RCT by de Leede et al . which found that the addition of chewing gum to an institutionalized ERP following elective abdominal surgery did not decrease the LOS, time to first flatus or time to first defecation.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The evidence, however, was considered to be of low quality and limited external validity, owing to small sample sizes (with the average number of patients per trial ranging from 20 to 50), the absence of a perioperative ERPs setting and the limited diversity of surgical procedures. The results of this review have also since been refuted by a recent large multicentre RCT by de Leede et al . which found that the addition of chewing gum to an institutionalized ERP following elective abdominal surgery did not decrease the LOS, time to first flatus or time to first defecation.…”
Section: Discussionmentioning
confidence: 80%
“…As per the evidence strength assessment reported in the included studies, the evidence for oral laxatives, including magnesium‐based laxatives was reported to be weak for all outcome measures. The evidence for chewing gum in achieving the return of GI function changed from moderate/strong in earlier papers to weak in later papers because of available newer evidence . Alvimopan was reported to have moderate to strong evidence for improving return of GI function, reduction in the incidence of ileus, and reduced day stay, especially in patients undergoing laparotomy …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two old favourites resurfaced on Twitter last month: an RCT from last year on the role of chewing gum for ileus after abdominal surgery (tweeted by Stephen Chapman, @SJ_Chapman), and Mokhles et al . 's paper from 2016 on colorectal cancer follow‐up after potentially curative resection, discussed at the Exeter Journal Club.…”
mentioning
confidence: 99%